PROFIL KETERAMPILAN PEMECAHAN MASALAH SECARA KREATIF SISWA SMA PADA POKOK BAHASAN LISTRIK DINAMIS - Busyairi, Ahmad; Sinaga, Parlindungan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Creative problem solving skills are very important to well posted, either by scientists, employees, teachers, and other professions. A nation will be able to win the global competition if the nation has a creative problem solving skills. Therefore, creative problem solving skills need to be trained in schools. Observations results show that the creative problem solving skills still seems to be less attention so that profile less known. This research aim to determine profile of creative problem solving skills of students in particular the problem relatied to application concept of electric fields. The research method used is descriptive method. The subject of this research are 30 students at high school in Bandung regency. The research instrument is a test that device creative problem solving skills in essay form. Indicator mesured consist of four skill aspects are; fact finding, problems finding, idea finding, and solution finding. Data have analyzed by calculating the average score of all students have interpreted with the criteria that have been made by Brookhart. The results show that the creative problem solving skills of students is still relatively low, especially in problems finding, ideas finding, and solutions finding. Kata kunci: creative thinking skills, problem solving, electric fields.